Resonant optical Stark effect in monolayer WS(2) - Cunningham, Paul D. (Nat Commun, 2019)
Breaking the valley degeneracy in monolayer transition metal dichalcogenides through the valley-selective optical Stark effect (OSE) can be exploited for classical and quantum valleytronic operations such as coherent manipulation of valley superposition states. The strong light-matter interactions responsible for the OSE have historically been described by a two-level dressed-atom model, which assumes noninteracting particles. Here we experimentally show that this model, which works well in semiconductors far from resonance, does not apply for excitation near the exciton resonance in monolayer WS(2). Instead, we show that an excitonic model of the OSE, which includes many-body Coulomb interactions, is required. We confirm the prediction from this theory that many-body effects between virtual excitons produce a dominant blue-shift for photoexcitation detuned from resonance by less than the exciton binding energy. As such, we suggest that our findings are general to low-dimensional semiconductors that support bound excitons and other many-body Coulomb interactions.